Analysis of the Effect of Social Media on Teenage Premarital Sex at SMAN 8 in Jambi City - Lia Permata Sari; Fatma Sylvana Dewi; Endang Maryanti (Journal La Medihealtico, 2021)
In the era of globalization, the dissemination of information is done quickly and easily. The development of technology is the background of this condition. This study aims to determine the effect of social media on adolescent premarital sex in SMA Negeri 8 Jambi City. This design is a qualitative research with a phenomenological approach. Data collection methods of observation, interviews, and documentation. The key informants of the research were 2 students and 1 BK teacher with supporting informants from parents, friends outside of school, school friends and informants' boyfriends and continued in a synergistic comprehensive manner involving stakeholders and grassroots. The results of in-depth interviews found that the condition of teenagers at SMA Negeri 8 Jambi City was well behaved, students' media exposure using social media such as whatsapp, instagram, youtube via cellphone for daily activities in doing school assignments, students acknowledged a change in behavior after using social media and towards premarital sex teenagers consider holding hands with the opposite sex is normal. Social media conclusions have an influence on them by imitating what they see that changes their behavior and way of thinking in carrying out their roles as teenagers. It is recommended that the school improve supervision of students in the use of cellphones during school hours, and Adolescent Reproductive Health and Information communication officers increase the intensity of visits to schools to disseminate wisdom in the use of social media